THE IMPORTANCE OF EMOTIONAL INTELLIGENCE IN PREVENTING PROFESSIONAL BURNOUT AMONG TEACHERS - Barno Rustamova (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2026)
Teaching is considered one of the most emotionally demanding professions in modern society. Teachers constantly interact with students, parents, colleagues, and administrators, which often leads to emotional stress and psychological exhaustion. This article examines the relationship between emotional intelligence and professional burnout among teachers. Emotional intelligence is described as the ability to understand, manage, and regulate emotions effectively, while professional burnout refers to emotional exhaustion, depersonalization, and reduced professional achievement caused by long-term stress. The article discusses the importance of emotional intelligence in pedagogical activity, the major causes and consequences of burnout, and practical strategies for preventing emotional exhaustion among teachers. The study highlights that teachers with high emotional intelligence demonstrate stronger stress resistance, better communication skills, higher professional motivation, and greater psychological well-being. The article concludes that developing emotional intelligence is an important way to improve teachers’ professional effectiveness and maintain healthy educational environments.